ANALISIS KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) PADA PT. HM SAMPOERNA TBK. TAHUN 2013-2022 - Dona Elvia Desi; Faizal Edwin (Jurnal Ekonomi Sakti, 2023)
This study aims to measure and analyze financial performance using the Economic Value Added (EVA) and Market Value Added (MVA) methods in cigarette companies, namely PT HM Sampoerna Tbk." This type of research is descriptive research with a quantitative approach. This research uses secondary data in the form of financial statements of PT HM Sampoerna Tbk for the period 2013-2022 published on the Indonesia Stock Exchange" as well as share prices on Yahoo Finance. "The results of research by cigarette company PT HM Sampoerna Tbk show a positive values (>0) EVA and MVA, meaning that PT HM Sampoerna Tbk has been able to create added value or the resulting profit has been able to meet expectations for the company's shareholders (investors) and is able to create or increase the value of capital that has been invested by funders". Although PT HM Sampoerna Tbk has increased and decreased, the MVA calculation from 2013-2022 always shows positive results.